2014
DOI: 10.1021/mp500290f
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Nanogel Conjugate for Improved Stability and Cellular Permeability of Curcumin: Synthesis, Pharmacokinetics, and Tumor Growth Inhibition

Abstract: Curcumin (CUR) is a unique natural compound with promising anticancer and anti-inflammatory activities. However, the therapeutic efficacy of curcumin was challenged in clinical trials, mostly due to its low bioavailability, rapid metabolism, and elimination. We designed a nanodrug form of curcumin, which makes it stable and substantially enhances cellular permeability and anticancer activity at standard oral administration. Curcumin was conjugated as an ester to cholesteryl-hyaluronic acid (CHA) nanogel that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(39 citation statements)
references
References 33 publications
(92 reference statements)
1
37
0
1
Order By: Relevance
“…It has been reported that the stability of curcumin increases when bound to plasma proteins or loaded in nanoformulations (39)(40)(41). We therefore studied the degradation of curcumin in two different formulations, namely loaded in mPEG-HPMA-Bz micelles and in Triton X-100 micelles.…”
Section: Degradation Of Curcumin (As Curcuminoid Mixture) Loaded In Mmentioning
confidence: 99%
“…It has been reported that the stability of curcumin increases when bound to plasma proteins or loaded in nanoformulations (39)(40)(41). We therefore studied the degradation of curcumin in two different formulations, namely loaded in mPEG-HPMA-Bz micelles and in Triton X-100 micelles.…”
Section: Degradation Of Curcumin (As Curcuminoid Mixture) Loaded In Mmentioning
confidence: 99%
“…Shinde and Devarajan 27 reported that microemulsions composed of docosahexaenoic acid could effectively deliver CUR to the brain and inhibit the growth of human glioblastoma U-87MG cell line in vitro. Wei et al 28 demonstrated that cholesteryl-hyaluronic acid nanogel of CUR exhibited excellent solubility and sustained drug release under physiological conditions and effectively inhibited human pancreatic adenocarcinoma MiaPaCa-2 cells. Jyoti et al 29 investigated chitosan (CS) microspheres of CUR and showed that the microspheres improved solubility and therapeutic index of CUR in HT-29 cells.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that curcumin is a lipophilic molecule and has been extensively used in food, medicines, and cosmetics due to its various bioactivities [17][18][19][20][21]. However, its delivery is highly limited by its insolubility and instability in biological fluids [22][23][24][25]. So far, it is yet to fulfill its clinical promise in part due to pH-mediated instability [26].…”
Section: Introductionmentioning
confidence: 99%